Pengaruh Luas Lahan, Jumlah Produksi, dan Kurs Dollar pada Ekspor Cengkeh di Indonesia - Manik Segarani, Luh Putu; Martini Dewi, Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 4, April 2015 (pp. 220 - 348), 2015)
The clove is one of the 15 commodities are preferred in plantation development, especially for domestic needs. And clove is a mainstay of Indonesia's non-oil commodities. Domestic yields fluctuated so as to affect the export volume of cloves out of the country. The purpose of this study was to determine the effect of land area, the amount of production, and the dollar exchange rate on exports of cloves in Indonesia in 1993-201 2 . Data analysis techniques using multiple linear regression. The results showed land area, the amount of production and the US dollar exchange rate simultaneously significant effect on export volumes cengekeh in Indonesia in 1993-2012. For Partial Test consists of land area, the amount of production and the US dollar exchange rate partially significant effect on the volume of exports of cloves in Indonesia in 1993-2012.
Keywords: luas lahan, ekspor, jumlah produksi